Analysis of the Efficiency of Raw Material Inventory Control at Tofu Factory ST12 Pasirmulya Karawang - Nur Ocravia, Julia Anisa; Mohammad Darul Fadli, Uus; Ery , Rosmawati (Research in Management of Technology and Business, 2024)
Inventory is important in the running of a business, both in large and small businesses. The purpose of this study is to gain a deeper understanding and conduct an analysis related to the control of raw materials compare the control of soybean raw material stocks and find out how much the cost difference is between the calculation in the control method and the company's calculation. The research is quantitative descriptive research with a comparative study design. This research is located at ST12 Pasirmulya Tofu Factory in Karawang, West Java. Primary data was obtained from interviews, observations, and documentation and secondary data was obtained from books, previous research, online media and libraries. The author reviews inventory control to minimize costs and successfully bring significant profits to businesses or companies using a comparison of the EOQ method and the JIT method. The results showed that the costs incurred by ST12 Tofu Factory were greater than those using the EOQ and JIT methods. From the calculation results, it is found that JIT is more efficient than EOQ or the company's method because the amount of expenditure is minimal for both methods.